Análise comparativa do proteoma do músculo Longissimus dorsi em ovinos da raça Morada Nova e Santa Inês alimentados com farelo de soja, farelo de mamona não peneirado e farelo de mamona peneirado - Magalhães, Iury Lima Aragão (2021)
Diet can influence animal performance and muscle protein expression, impacting meat quality. In the present study, proteomic profiles of the Longissimus dorsi muscle of Morada Nova and Santa Inês male sheep fed with three different diets: containing soybean bran (FS), detoxified castor bean bran (FMP) and detoxified sifted castor bean bran (FMDP) were evaluated using one-dimensional SDS-PAGE electrophoresis and computational analyses, followed by LC-MS and gene ontology analyses. The objective of this work was to carry out a comparative analysis between the proteomes obtained from the analyzes of the L. dorsi muscle in the three different dietary compositions. Animal performance data were previously published, showing no significant differences (p < 0.05) in weight gain and feed conversion. In proteomic profiles, the FMDP-fed Santa Inês breed showed an increase in the expression of proteins linked to the glycolytic pathway (CMK, ENO3, PGKA1) and structural proteins (ACTA1) in band 11 (52 kDa) that act directly on post mortem alterations, which can impact on meat quality. For the Morada Nova breed, 22 bands and 70 proteins were detected, for the Santa Inês breed, 25 bands and 68 proteins were detected. Analyzes in silico were performed using the STRING database 10.0 for differential band proteins. In conclusion, according to the methodology used in this work, the diet with inclusion of FMDP showed a slight alteration in the protein profile of the L. dorsi muscle.